(untitled) (International relations and international law Journal, 2018)
China officially proposed the strategy ‘one belt one road’ in 2013, which aims to jointly faciliate the regional economic intergration by strengthening cooperation with neighboring countries. After the strategy ‘one belt one road’ had been proposed, Kazakhstan, as a necessary part of the Silk Road, and China will develop further exchange and communication in economics, politics, culture. The geographical location of China and Kazakhstan are border to each other and their resources can complement each other’s needs. These conditions give important opportunity and juncture for two countries on trade cooperation and mutual investment. The aim of this article is to reveal the main problems of trade cooperation between China and Kazakhstan. This article takes the industrial cooperation between China and Kazakhstan as the research object, analyzes the current trade between China and Kazakhstan and the significance of industrial cooperation. Methodology of the article consists of mathematical analysis, scientific analysis and synthesis, statistical methods, historical method. Finally discuss the further opportunities for economic and trade cooperation between the two countries according to the current economic situation. The main conclusion of the article consists of idea that Kazakhstan and China need to deepen and expand their trade relations. Key words: Trade cooperation, industry cooperation, one belt one road, Kazakhstan.